2012
DOI: 10.1177/0748233712463779
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of Vernonia cinerea in vincristine-induced painful neuropathy in rats

Abstract: The present study was designed to investigate the antinociceptive potential of Vernonia cinerea (VC) on vincristine-induced painful neuropathy in rats. A chemotherapeutic agent, vincristine (50 μg/kg intraperitoneally for 10 consecutive days), was administered for the induction of neuropathic pain in rats. The painful behavioral changes were assessed using hot plate, acetone drop, paw pressure, Von Frey hair and tail immersion tests to assess the degree of hyperalgesic and allodynic pain sensation in paw and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…Vincristine-injected mice also displayed functional (SFI) loss and oxidative stress in sciatic nerve in the present study. Pregabalin, a selective Ca v 2.2 (a2 -d subunit) channel antagonist, was used as a standard and protected the vincristine-induced hyperalgesic response in this study, which is in accord with previous report (Thiagarajan et al, 2012). In the present study, treatment with curcumin in vincristine-injected mice significantly increased the nociceptive threshold, decreased the oxidative stress and total calcium levels, and improved functional index in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 80%
“…Vincristine-injected mice also displayed functional (SFI) loss and oxidative stress in sciatic nerve in the present study. Pregabalin, a selective Ca v 2.2 (a2 -d subunit) channel antagonist, was used as a standard and protected the vincristine-induced hyperalgesic response in this study, which is in accord with previous report (Thiagarajan et al, 2012). In the present study, treatment with curcumin in vincristine-injected mice significantly increased the nociceptive threshold, decreased the oxidative stress and total calcium levels, and improved functional index in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 80%
“…16,50,51 Earlier reported data suggest that neuropathic pain has been linked with rise in neuronal calcium levels followed by enhance in the oxidative stress markers (free radicals) and inflammatory cytokines, etc. 50,52 Moreover, other mechanism which could be a possible reason behind vincristine-induced neuropathy are as follows: mitochondrial changes 53 ; increase in sodium ion current in DRG predisposing to paraesthesia and fasciculations 54 ; activation of calcium activated proteases calpains and caspases in DRG neurons 55 ; increase in 5-HT2A receptors on dorsal horn and DRG neurons 56 ; and dysfunction of the spinal NO/cGMP pathway. 57 In the present study, treatment with FA and GBA-attenuated vincristine induced alterations in nociceptive threshold (mechanical hyperalgesia, heat hyperalgesia, mechanical dynamic allodynia, and cold allodynia), electrophysiological changes (MNCV and SNCV), and histopathological analysis, suggesting its antinociceptive potential in vincristineinduced neuropathy.…”
Section: Discussionmentioning
confidence: 98%
“…Actually, neuropathic pain has been linked with a rise in neuronal calcium levels followed by enhancement of the oxidative stress markers (free radicals) and inflammatory cytokines, etc. 53 , 54 . This suggested that the inhibitory effect of MT on neuropathic pain might also be mediated by the calcium channels.…”
Section: Discussionmentioning
confidence: 99%